PENINGKATAN KETERSEDIAAN NUTRISI MIKRO PADA TANAMAN: UPAYA MENGURANGI MALNUTRISI PADA MANUSIA - Amalia Tetrani Sakya (Universitas Sebelas Maret, 2016)
Malnutrition is still one of the big problems the majority of developing countries including Indonesia. Malnutrition is the result of insufficient intake of available nutrients in the human diet. The availability of nutrients is mainly determined by the output of food produced from agricultural systems. Plants provide almost all the necessary vitamins and minerals, but due to low mineral content in staple crops, resulting in the intake becomes less and lead to malnutrition or lack of nutrients. Unfortunately, as a result of population pressure, a lot of the current global food system does not provide enough micronutrients to ensure adequate micronutrient intake for everyone. This has resulted in an increase in the prevalence of micro-nutrient deficiencies (for example, iron deficiency, vitamin A deficiency, and iodine), which now afflicts many poor women resources, infants and children in developing countries. To get a balanced nutrition and adequate then improve the quality of agriculture as a food ingredient indispensable. Various attempts to overcome nutritional deficiencies especially regarding micro nutrient deficiencies, such as supplementation, food fortification and diversification of the food has a lot to do, but did not provide maximum results. Another alternative approach to address the problem of shortage of micronutrients is biofortification, genetic biofortification or agronomic biofortification. This approach emerged due to health and human well-being depends entirely on the plants, either directly or indirectly.